Targeting the HSP60/10 chaperonin systems of Trypanosoma brucei as a strategy for treating African sleeping sickness. Issue 21 (1st November 2016) - Abdeen, Sanofar; Salim, Nilshad; Mammadova, Najiba; Summers, Corey M.; Goldsmith-Pestana, Karen; McMahon-Pratt, Diane; Schultz, Peter G.; Horwich, Arthur L.; Chapman, Eli; Johnson, Steven M.
Graphical abstract: Abstract: Trypanosoma brucei are protozoan parasites that cause African sleeping sickness in humans (also known as Human African Trypanosomiasis—HAT). Without treatment, T. brucei infections are fatal. There is an urgent need for new therapeutic strategies as current drugs are toxic, have complex treatment regimens, and are becoming less effective owing to rising antibiotic resistance in parasites. We hypothesize that targeting the HSP60/10 chaperonin systems in T. brucei is a viable anti-trypanosomal strategy as parasites rely on these stress response elements for their development and survival. We recently discovered several hundred inhibitors of the prototypical HSP60/10 chaperonin system from Escherichia coli, termed GroEL/ES. One of the most potent GroEL/ES inhibitors we discovered was compound1 . While examining the PubChem database, we found that a related analog, 2e - p, exhibited cytotoxicity to Leishmania major promastigotes, which are trypanosomatids highly related to Trypanosoma brucei . Through initial counter-screening, we found that compounds1 and2e - p were also cytotoxic to Trypanosoma brucei parasites (EC50  = 7.9 and 3.1 μM, respectively). These encouraging initial results prompted us to develop a library of inhibitor analogs and examine their anti-parasitic potential in vitro. Of the 49 new chaperonin inhibitors developed, 39% exhibit greater cytotoxicity to T. brucei parasites than parent compound1 . While many analogs exhibit moderate cytotoxicity to human liver and kidney cells, we identified molecular substructures to pursue for further medicinal chemistry optimization to increase the therapeutic windows of this novel class of chaperonin-targeting anti-parasitic candidates. An intriguing finding from this study is that suramin, the first-line drug for treating early stage T. brucei infections, is also a potent inhibitor of GroEL/ES and HSP60/10 chaperonin systems.